The Impact of Organizational Culture on Turnover Intention and Employee Engagement as Intervening Variable - Veritia Veritia; Anoesyirwan Moeins; Widodo Sunaryo (The Eastasouth Management and Business, 2026)
A significant number of employees still intend to change employment. This study seeks to investigate the impact of organizational culture and employee engagement on turnover intention. This research used a mixed-methods approach. Mixed Methods is a research approach that integrates quantitative and qualitative research methodologies. This research employs a sequential explanatory design, first with quantitative methods and subsequently integrating qualitative approaches to compare the average outcomes of both. This study encompasses an accessible population of 1,960 enterprises and a manageable population of 321 employees from the Palm Oil Company Group in Indonesia. The study sample comprised 179 employees. The results are as follows: Organizational culture adversely affects turnover intention. Employee engagement adversely influences turnover intention. Organizational culture exerts a favorable influence on employee engagement. The organizational culture adversely affects turnover intention via employee engagement as a mediating variable.